Hedonisme dan Krisis Moral dalam Hukum: Analisis Filsafat Hukum Terhadap Degradasi Nilai Keadilan di Era Modern - Ramania, Hasya; Riser, Muh. Abriel Gifari; Ramadhan, Adam; Lesmana, Jordanno; Adrian, Enrico (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
The development of modern society, characterized by technological advancement, globalization, and shifting social interactions, has led to the emergence of a pleasure-oriented lifestyle known as hedonism. This phenomenon not only influences individual behavior but also affects the legal system, particularly in terms of morality and justice. This article aims to analyze the relationship between hedonism and the moral crisis in law, as well as its implications for the degradation of justice values from a legal philosophical perspective. This research employs a normative legal method with conceptual and philosophical approaches, examining utilitarianism, theories of justice, and virtue ethics. Furthermore, this study incorporates the assault case involving David Ozora as an empirical reflection of the moral crisis in modern society. The findings indicate that the dominance of hedonistic values tends to shift the orientation of law from substantive justice toward pragmatic interests and subjective satisfaction, thereby weakening the moral legitimacy of law. Therefore, it is necessary to reinforce the moral dimension of law to ensure the realization of fair and balanced justice. Practically, this study urges legal practitioners and policymakers to re-integrate ethical education and strict moral considerations into law enforcement processes to prevent further degradation of the justice system.